Tata Pamer Museum Negeri Pada Masa Lalu Dan Masa Kini: Studi Museum Nasional Indonesia dan Museum Sonobudoyo - Ashar Murdihastomo; Dimas Seno Bismoko; Rama Putra Siswantara (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
The museum is a dynamic institution and always developed according to its time. The development of the museum is intended so that the museum can always be accepted by the public. The display system of the museum is referred to as one of the most visible parts of the development of the museum because it has a crucial value and can be an indication of the condition of society at that time. Indonesia had experienced at least three periods of development, namely the colonial period, the independence period, and the post-reformation period (present). This question aims to see the compatibility between the participation of the museum and the development of the community. This article used two data, primary and secondary data. The primary data were obtained from direct observation, while secondary data was derived from a literature study. The data is then described, comparatively explanatively analyzed, and then interpreted. The results of the interpretation are then used to answer the questions posed. The conclusion obtained is that the exhibition system in the colonial period was associated with efforts to study Indonesian cultural objects, the exhibition system during the independence period was intended to spread the nation's ideology, and the post-reformation period emphasized the social role of museums to society. Keywords: museum; colonial; independence; post-reformation